Analisis Konsep dan Peran Pendidikan Karakter dalam Pengembangan Sikap Siswa: Studi Literatur dalam Konteks Madrasah - Misrina, Misrina; Nasir, Khairun; Diana, Diana (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This research discusses the concept of character building and the role of character building in developing students' attitudes in schools. The concept of character building encompasses values, attitudes, and positive behaviors that are the primary focus of developing good personality traits in individuals. Character building is based on the idea that character can be taught, learned, and applied in daily life. This concept is also supported by the moral philosophy introduced by Al-Ghazali and Ibn Maskawaih, emphasizing the importance of moral education in shaping good character. Furthermore, the research method employed in this study includes a literature review and content analysis. Some data were collected from various sources related to the concept of character building and the role of character building in developing students' attitudes in a madrasah (school). The data were analyzed descriptively to explore the relationships between these concepts and their implications in the context of education in madrasahs. The findings of the research indicate that character building plays a crucial role in developing students' attitudes in madrasahs. By integrating character concepts from Lickona with moral concepts from Al-Ghazali and Ibn Maskawaih, madrasahs can shape a generation with character and noble morals in accordance with Islamic teachings. The implications of this research suggest that character building needs to be a primary focus in madrasah education to mold individuals who are ethical, responsible, and beneficial to religion, society, and the nation.